Unconventional monetary policy under review: Past, present and future challenges - Robert Holzmann (Oesterreichische Nationalbank (OeNB), 2024)
After the global financial crisis and until 2021, the primary objective of central banks in advanced economies was to implement policies aimed at increasing inflation, given that inflation had been too low for too long. Having reached the effective lower bound (ELB) of nominal interest rates, monetary policy had to resort to unconventional monetary policy (UMP) measures, which were not without negative side effects. In response to the rise in inflation in 2021, central banks returned to policy interest rates as their primary monetary policy tool and began to unwind their set of UMP measures. Assuming that inflation has been tamed, will we be able to maintain sufficient distance from the ELB to rely broadly on policy rates? Or will we again be forced to implement UMP with all its side effects and proportionality issues? Part I of the paper outlines the rationale and instruments of UMP: how it was supposed to work and how it actually worked, including its negative side effects. Part II considers alternative monetary policy options in a low inflation environment that prove limited and little convincing. The paper ends by discussing how prolonged use of UMP impacts on central bank profitability and central bank independence, also offering possible remedies.
Keywords: E52; E58; E43; 330; central banking; ECB; effective lower bound; monetary policy instruments; conventional and unconventional measures